2014
DOI: 10.1136/bcr-2014-203924
|View full text |Cite
|
Sign up to set email alerts
|

Brachial artery pseudoaneurysm

Abstract: We describe a case of an elderly man who presented with an upper arm swelling that had developed following a humeral fracture 8 months previously. The swelling was painless but associated with significantly diminished motor function of his right hand and concurrent paraesthaesia. On examination, a large pulsatile mass was identified and CT angiography confirmed the presence of an 11×7 cm brachial artery pseudoaneurysm. The patient underwent surgical repair in which a fragment of the humerus was found to have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Even though it is uncommon, the development of pseudoaneurysms is slow and can cause delayed diagnosis with further possible complications. Pseudoaneurysms, depending on the size, can be asymptomatic or present with symptoms ranging from pressure effect on the adjacent tissues such as pain, swelling, and nerve injury, or ischemic complications due to thrombosis or distal embolization with the management depending on the location, size, and causative pathogenesis of pseudoaneurysm [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it is uncommon, the development of pseudoaneurysms is slow and can cause delayed diagnosis with further possible complications. Pseudoaneurysms, depending on the size, can be asymptomatic or present with symptoms ranging from pressure effect on the adjacent tissues such as pain, swelling, and nerve injury, or ischemic complications due to thrombosis or distal embolization with the management depending on the location, size, and causative pathogenesis of pseudoaneurysm [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, he was transferred to the operating room for the surgical repair of the pseudoaneurysm. On close inspection during surgery, it was found that the sac contained a sharp fragment of the humerus with a single puncture wound in the brachial artery which was the reason for pseudoaneurysm formation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although predominantly described as secondary to iatrogenic causes, patientrelated factors may be considered, such as intravenous drug use or after sustaining a humeral fracture. [8][9][10] Brachial artery pseudoaneurysms 2 cm or less tend to be asymptomatic. 2 When symptomatic, they often present with a pulsating mass and local tenderness.…”
Section: Discussionmentioning
confidence: 99%
“…Although predominantly described as secondary to iatrogenic causes, patient-related factors may be considered, such as intravenous drug use or after sustaining a humeral fracture. 8 10…”
Section: Discussionmentioning
confidence: 99%
“…[7] Isolated aneurysm of the brachial artery in BD has been scarcely reported in the literature with only a couple of cases published in 1988 and 1993. [8,9] Koksoy et al [6] operated 29 aneurysms in BD patients. In their series, all aneurysms appeared to be pseudo-aneurysms.…”
Section: Discussionmentioning
confidence: 99%